PARP inhibitors in the treatment of ARID1A mutant ovarian clear cell cancer: PI3K/Akt1-dependent mechanism of synthetic lethality - Yakovlev, Vasily A.; Sullivan, Stephanie A.; Fields, Emma C.; Temkin, Sarah M. (Frontiers in Oncology, 2023)
Poly(ADP-ribose) polymerase (PARP) is a nuclear enzyme involved in the repair of DNA single-strand breaks (SSB). The recent development of poly(ADP-ribose) polymerase inhibitors (PARPi) results from over 45 years of studies. When the activity of PARP1 or PARP2 is compromised, DNA SSB lesions are unresolved and can be converted to DNA double-strand breaks (DSBs) by the cellular transcription mechanisms. ARID1A (also called BAF250a) is an important component of the mammalian Switch/Sucrose Non-Fermentable (SWI/SNF) chromatin-remodeling complex. ARID1A gene demonstrates >50% of mutation rate in ovarian clear-cell carcinomas (OCCC). Mutated or downregulated ARID1A significantly compromises the Homologous Recombination Repair (HRR) of DNA DSB. The present study demonstrated that downregulated or mutated ARID1A attenuates DNA HRR through stimulation of the PI3K/Akt1 pathway and makes tumor cells highly sensitive to PARPi and PARPi/ionizing radiation (IR) combination. We showed that PI3K/Akt1 pathway plays an important role in the sensitization of cancer cell lines with compromised function of ARID1A to PARPi treatment. We believe that using of PARPi monotherapy or in combination with radiation therapy is an appealing strategy for treating ARID1A-mutated cancers, as well as many other types of PI3K/Akt1-driven cancers.